The linguistic means of persuasive communication in the election campaign discourse - J Baghana; E A Bocharova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2009)
The article discusses the linguistic means of the speaker's influence on the audience in order to persuade them. The article is based on the public speeches transcripts of Barack Obama, John McCain and Dmitrii Medvedev in 2007-2008.